Measurement of particulate matter in a heritage building using optical counters: Long-term and spatial analyses - Saraiva, Nuno Francisco Baía da Silva Garcia (2023)
The good conservation of cultural patrimony depends on the quality of the indoor environment where collections and artifacts are kept, being suspended particles one of the key parameters. Among the various methods to study indoor pollution, portable optical counters appear as effective instruments to measure indoor pollution due to their specifications (low visual and acoustic impact). However, it is still one of the least common approaches when assessing the conservation quality in heritage buildings. Therefore, the present study focuses on developing a methodology that uses portable particle counters to monitor particulate matter inside historic buildings and assess indoor conservation quality. Long-term and spatial analyses were conducted using this type of equipment to identify causes of pollution in a case study, the Joanina Library in Coimbra, Portugal. Estimation of night concentrations was carried out as a complementary approach to the monitoring. A new conservation method of classifying indoor pollution was proposed as an alternative to the most common standards. This classification determines four conservation classes (A, B, C, and D) according to particulate matter and the respective percentage of time that measurements are within such classes. As a result, the measurements showed a poor indoor environment quality meeting the requirements of low-level classes, which are those with a greater risk of degradation (Classes C and D). The continuous long-term campaign of four years was decisive for the identification of the main sources and environmental conditions of higher pollution: the exterior pavement, the number of tourists, the use of carpets, and the absence of rain. The spatial results depend on the diameters of the particles and the space's height where the assessment is made. Thus, this type of device and the developed methodology could be used by curators as an effective tool for long-term and spatial assessment in this building typology.